Lead and chromium removal from leachate using horsetail (Equisetum hyemale) - E Kurniati; T Imai; T Higuchi; M Sekine (Journal of Degraded and Mining Lands Management, 2014)
Phytoremediation has been widely used for wastewater treatment technology. Horsetail was investigated for its capacity to remediate lead and chromium in leachate. This plant seemed to be an effective choice for phytoremediation due to its survival in extreme to moderate conditions, the availability of annual or perennial varieties and a deep root system. Conducted in a greenhouse, this research used leachate from final disposal. The leachate was exposed to six treated plants with three multiplications using activated natural zeolite media for one month. The treatments were flow system i.e. batch and continue, and living plants weight that is 0, 153 and 306 g planted in 20 cm diameter and 30 cm deep pots. The leachate pH, temperature, lead, and chromium concentration were observed and also the surrounding temperature and humidity. Results showed that 82.2% of lead can be removed by 153 gram horsetail on batch system as well as 61.2% chromium removal by 153 gram horsetail on continue system. Horsetail seemed to have future to be applied in phytoremediation of artisanal and small scale mining waste.